Is there ochratoxin A in “passito” dessert wines from Friuli? - TORELLI, EMANUELA; LOCCI, ROMANO (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2007)
The fungal mycoflora of dried grapes, used in Friuli for the production of “passito” dessert wines, was investigated to detect potential ochratoxin A (OTA)-producers, in particular species of the genera Penicillium and Aspergillus. From samples of five cultivars of grapevines, grown in different locations, 379 strains of Penicillium spp. were isolated, but not one from the genus Aspergillus. Four strains produced UV fluorescent metabolites, as detected by thin-layer chromatography (TLC), on grape juice agar and on synthetic liquid media. Three of these were OTA producers, when analyzed by high pressure liquid chromatography (HPLC), following immunoaffinity column purification. On the basis of morphocultural characteristics and ribosomal DNA sequencing, the strains were classified as P. puberulum and P. variabile. None appeared to belong to the species P. verrucosum or P. nordicum.